PENGARUHÃÂ SARANAÃÂ DANÃÂ PRASARANAÃÂ BELAJARÃÂ TERHADAPÃÂ HASILÃÂ BELAJARÃÂ MATAÃÂ PELAJARANÃÂ ALATÃÂ UKURÃÂ ÃÂ ÃÂ - SetiadiÃƒÂ‚Ã‚Â , -; Eko, Budiarso; Suwahyo, - (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2008)
Permasalahan ÃÂ dalam ÃÂ penelitian ÃÂ ini ÃÂ adalah ÃÂ seberapa ÃÂ besar ÃÂ pengaruh ÃÂ sarana ÃÂ dan ÃÂ prasarana ÃÂ praktikÃÂ belajar ÃÂ dengan ÃÂ ÃÂ hasil ÃÂ belajar ÃÂ mata ÃÂ diklat ÃÂ ÃÂ alat ÃÂ ukur, ÃÂ dan ÃÂ berapakah ÃÂ besaran ÃÂ kontribusinya. ÃÂ Populasi ÃÂ dalamÃÂ penelitian ÃÂ ini ÃÂ adalah ÃÂ 85 ÃÂ orang ÃÂ siswa ÃÂ kelas ÃÂ I ÃÂ program ÃÂ keahlian ÃÂ teknik ÃÂ mekanik ÃÂ otomotif. ÃÂ Pengambilan ÃÂ sampelÃÂ sebanyak ÃÂ 62 ÃÂ orang ÃÂ siswa ÃÂ menggunakan ÃÂ Normogram ÃÂ Harry ÃÂ King ÃÂ dengan ÃÂ teknik ÃÂ random ÃÂ sampling. ÃÂ MetodeÃÂ pengumpulan ÃÂ data menggunakan ÃÂ dokumentasi, ÃÂ observasi ÃÂ dan ÃÂ tes. ÃÂ Hasil ÃÂ penelitian menunjukkan ÃÂ ada ÃÂ pengaruhÃÂ antara sarana dan prasarana belajar terhadap hasil belajar sebesar 0,6886 (kuat). Hasil penelitian juga menunjukanÃÂ kondisi ÃÂ sarana ÃÂ dan ÃÂ prasarana ÃÂ praktik ÃÂ belajar ÃÂ sebesar ÃÂ 71,83% ÃÂ dalam ÃÂ kategori ÃÂ baik, maka ÃÂ prestasi ÃÂ belajar ÃÂ siswaÃÂ dalam alat ukur ÃÂ linier yang diperoleh masuk dalam kategori baik. Besaran kontribusi pengaruh yang terjadi padaÃÂ sarana dan prasarana praktik terhadap hasil belajar alat ukur liner adalah 47,42%.Kata kunci: Sarana, prasarana, praktikum, alat ukurÃÂ The ÃÂ problem ÃÂ containing ÃÂ in ÃÂ this ÃÂ research ÃÂ is ÃÂ how ÃÂ much ÃÂ the ÃÂ effect ÃÂ of ÃÂ study ÃÂ practice ÃÂ facilities ÃÂ andÃÂ infrastructures ÃÂ toward ÃÂ study ÃÂ result ÃÂ in ÃÂ measuring ÃÂ tool ÃÂ training ÃÂ subject ÃÂ is, ÃÂ and ÃÂ how ÃÂ much ÃÂ the ÃÂ contributionÃÂ magnitude ÃÂ is. The population of ÃÂ the research was about 85 ÃÂ first graders of automotive mechanical skill program.ÃÂ The sample of it was approximately 62 students using Normogram Harry King with random sampling ÃÂ technique.ÃÂ Data was collected using methods such as documentation, observation, and test. Research result shows that studyÃÂ facilities and infrastructures brings around 0,6886 toward study result (strong). Other result is that study facilitiesÃÂ and infrastructures are 71,83% in good category. Hence, studentsÃ¢â¬â¢ study achievements using linier measuring toolÃÂ are also in good category. The magnitude of effect happening in practice facilities and infrastructures toward studyÃÂ result using linier measuring tool is about 47,42%.Keywords: facilities, infrastructures, practice, measuring tool